TIRE MUSCLE - I. lmani, N. (2002)
He articulates it presents a new actuador that has revolutionized the construction of industrial machines, you structure industrial and included diverse applications the civil engineering. The pneumatic muscle is a traction actuador that works as a human muscle and it is able to generate a force of initial but big traction that that of the conventional pneumatic cylinders. He/she stands out in the l articulate, their principles, their utilities, advantages, applications and technical characteristics.